Friction stir weave welding (FSWW) of AA6061 aluminium alloy with a novel tool-path pattern. Issue 2 (4th May 2019) - Jayabalakrishnan, D.; Balasubramanian, M.
Abstract: In this present work, a novel tool-path movement has been implemented in the friction stir welding of AA6061-T6 plates and termed as Friction stir weave welding (FSWW). The aim of this new process is to enhance the weld quality in terms of tensile strength and microstructure properties by the selection of effective process parameters, such as tool-path movements (Step size), spindle speed and weaving rate. The investigation results proved that the tensile strength of AA6061-T6 alloy joints were remarkably affected by the newly developed tool-path pattern. A three factor, three-level Box–Behnken design matrix was used to minimise the number of experiments. A response surface methodology technique was used for developing the objective function. TOPSIS technique was applied to optimise the FSWW process parameters. The optimised results were validated with the derived experimental results.